A NMR analysis of urine samples obtained from swimming athletes at the 2006 Doha Asian Games - Li, J.; Li, C.; Xu, X. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. I, 2008)
Scientists have attempted to determine the factors that create a world-class athlete, by using physiology, biochemistry, histology, and genetic engineering techniques (Myburgh, 2003). However, the above mentioned methods are not effective as performance predictors among relatively homogenous groups of well-trained elite or even sub-elite athletes (Myburgh, 2003). This paper demonstrates determination of athletic potential may be possible through analyzing athletes` urine with nuclear magnetic resonance (NMR) spectroscopy.